Glibenclamide - hibiscus rosa sinensis leaves water extract effects on streptozotocin induced diabetic rats / Farah Adilah Taib - Taib, Farah Adilah (2014)
Due to increases in prevalence of diabetes mellitus the numbers of people using complementary and alternative medicine are increasing nowadays. Diabetic patient always searching for other alternative to lower their blood glucose level, this lead them in consuming herbs and plants which is believed having hypoglycemic effect together with medicine prescribe by physician. In this project, we study the effect of drug-herb interaction of glibenclamide and Hibiscus rosa sinensis water extract on streptozotocin induced diabetic rats. Blood glucose, body weight, food consumption and pancreas histology were determined in streptozotocin induced diabetic rats using 30 male Wistar rats. The rats were randomly divided into 5 groups of 6 rats each. The rats were induced with diabetes by administering streptozotocin 40mg/kg intraperitoneally. Treatment is given for 28 consecutive days. Oral glucose tolerance test is done as to confirm rats with low blood glucose are diabetic after administration of streptozotocin. There was significance difference between positive control group and the combination treatment group in lowering blood glucose level and increasing body weight while no significance different in food intake. Result of histology study showed prevention of further destructive of pancreatic cell of the combination treatment compared with positive group and thus improve the size, structure and number of p cells. As a conclusion, repeated administration of the glibenclamide (0.5 mg/kg) and extract at an oral dose equivalent to 125 mg/kg, (once daily for 28 consecutive days), can give better hypoglycemic effect compared to treatment of glibenclamide alone. There were also increased in number of p cells of pancreatic Islet of Langerhans observed upon conduction histological study on the pancreas cell.